Dairy cattle welfare: knowledge, attitudes and practices of stockpeople from Midlands Province-Zimbabwe’s large-scale dairy farms - Zivanayi Matore; Pamela Woods; Tonderai Mutibvu (BMC Veterinary Research)
Abstract Welfare of dairy animals and consequently their health and productivity is influenced by numerous factors such as the quality and quantity of supplement, health care given to animals, and stockpeople Knowledge, Attitudes and Practices (KAP) on animal welfare. A lot of studies have been conducted to evaluate the influence of most of the above factors on welfare of dairy animals, but very little studies focused on the influence of stockpeople KAPs of animal welfare. However, given the growing demand for milk and dairy products and the increasing global demand for animal products that are produced in an animal welfare friendly environment there is potential benefit of studying the KAPs of stockpeople towards the welfare of dairy animals. Herein, a cross sectional study involving 93 stockpeople from the 31 large-scale dairy farms in Midlands Province, Zimbabwe was conducted to determine their KAPs on animal welfare. Results of this study revealed that 67% of the stockpeople could not define animal welfare and this was significantly associated with the stockperson’s level of education (χ2 = 12.54, df = 3, p = 0.006). Only 14% of the stockpeople interviewed always talked to dairy animals when handling them and this was correlated with gender (p < 0.001). About 20% of the stockpeople responded positively to touching the dairy animals when handling them and this was associated significantly with the stockperson’s gender (p = 0.005). On a more positive note when stockpeople were asked to respond to whipping of animals when driving them, about 90% of the stockpeople said they never whip animals when handling or driving them. It is recommended that further studies be done to find out better and more effective ways of teaching animal welfare concepts and practices. These approaches of teaching animal welfare to stockpeople should take into account the stockpeople’s cultural, religious and education backgrounds. Stockpeope due to their low renumeration may also prioritise animal welfare attributes that directly impact on production such as hunger and thirst as well freedom from diseases pain and injury.